Pengolahan Limbah Plastik Menggunakan Reaktor Pirolisis di Bank Sampah Dream Central, Desa Wijaya Pura, Kecamatan Jambi Selatan, Kota Jambi - Lenny Marlinda; Rahmi Rahmi; Diah Riski Gusti; Intan Lestari; Wahyudi Zahar; Aditya Denny Prabawa; Yuli Evrianti Br Rajagukguk; Ermita Meisa Manulang; Ladiva Adinda; Rif’at Syauqi (Jurnal IPTEK Bagi Masyarakat, 2025)
The COVID-19 pandemic has increased online shopping and food delivery, causing a surge in single-use plastic waste and has become a habit to this day along with the rapid development of digital technology. Dream Central Waste Bank (BSI Dream) in Wijaya Pura Village collects 3 tons of waste monthly but lacked advanced plastic processing technology. This community service initiative aimed to implement a pyrolysis reactor to convert plastic waste into fuel oil and paving blocks, thereby enhancing economic value while promoting environmental sustainability. The activity stages included partner coordination and surveys, reactor performance upgrades, operational training, and evaluation. This activity involved five partners representing the Wijaya Pura Village community.  The reactor successfully produced fuel oil (density: 0.848–0.912 g/mL) and residues suitable for paving block production. The outcome of this initiative demonstrated improved skills among partners, the creation of marketable products and increased community income opportunities. Furthermore, the activity fostered greater awareness of the importance of sustainable waste management and supported the application of circular economy principles.